Impacts of Community Parks on Residents’ Health Benefits and Enhancement Strategies Thereof from the Perspective of Micro-Renewal: A Case Study of Nanjing - Tianyuan SHOU; Mingjuan ZHANG; Jiaxing WEI (Fengjing Yuanlin)
ObjectiveAs urbanization accelerates globally, cities are transitioning from incremental expansion to stock optimization, with urban renewal becoming crucial for enhancing urban quality. Community micro-renewal, emphasizing small-scale, precise, and gradual optimization, plays a significant role in this process. Community parks, as green spaces for daily leisure activities, satisfy social interaction and nature experience needs, and are vital for improving the environment in high-density urban areas. Previous research on community park micro-renewal mainly focuses on vegetation coverage, hard-surfaced space and species composition. While vegetation coverage has been widely studied, with tree canopy coverage often used as a key indicator, the role of hard-surfaced space has been relatively overlooked. Research on species richness and its perception has shown their potential to enhance health benefits, but empirical research on animal species perception beyond vegetation and birds remains limited. Also, most research has ignored the nonlinear effects of community park characteristics on health benefits due to the use of linear regression and other analytical ideas. Therefore, integrating vegetation coverage, hard-surfaced space, and animal species perception to evaluate the multidimensional characteristics of community parks and their non-linear impacts on residents’ health benefits has both theoretical value and practical support for community park design oriented at health benefits.MethodsThis research employs a comprehensive approach to investigate 34 community parks in Nanjing, China. A questionnaire survey is conducted, with 1,400 questionnaires distributed and 1,335 valid responses collected. The survey covers residents’ self-assessed health benefits, animal diversity perception, and socio-demographic factors. Tree canopy coverage and hard-surfaced space proportion are measured using high-resolution Google remote-sensing images dated July 2023, and then processed and analyzed with ENVI 5.3 and eCognition Developer 64 software. The generalized ordered logit models is utilized to analyze the non-linear effects of community park characteristics on residents’ health benefits, with socio-demographic factors such as gender, age, education level, and family income as control variables.ResultsThis research reveals a hierarchical and non-linear association between community park characteristics and residents’ self-assessed health benefits. When health benefit level is low, tree canopy coverage, animal species perception, and hard-surfaced space proportion all show positive associations with self-assessed health. However, as the health benefit level increases, the positive effects of these three indicators gradually decrease. Tree canopy coverage has significant positive impacts on the lower two health benefit levels but is not significant at the highest level. Hard-surfaced space proportion demonstrates significant positive effects across all the three health benefit levels, with the effect size diminishing as health benefit level increases. Animal species perception also exhibits significant positive effects at all levels, but the effect size decreases with the increase of health benefit level. Furthermore, hard-surfaced space proportion is found to have a more significant positive impact on health benefits compared to tree canopy coverage.ConclusionThis research concludes that community park characteristics have a non-linear impact on residents’ health benefits, with varying effects across different health benefit levels. First, tree canopy coverage, hard-surfaced space proportion, and animal species perception all exhibit positive associations with residents’ self-assessed health benefits, with their effects diminishing as health benefit level increases. Specifically, tree canopy coverage significantly influences lower health benefit levels, hard-surfaced space proportion positively impacts all health benefit levels with decreasing effect size, and animal species perception shows positive effects across all levels with similar diminishing patterns. Second, the research highlights the significant role of hard-surfaced space in community parks, showing that it has a more substantial positive impact on health benefits compared to tree canopy coverage, which suggests the irreplaceable role of hard-surfaced spaces in safeguarding health. Third, the research underscores the importance of animal species perception in improving health benefits, with the positive effects of perceiving diverse animal species in community parks being evident across all health benefit levels, implying that incorporating design elements that enhance biodiversity and facilitate positive human − animal interactions can significantly contribute to the health promoting potential of community parks. These findings provide valuable insights for urban planners and policymakers, suggesting that community park micro-renewal should focus on optimizing both green and hard-surfaced spaces while enhancing biodiversity to maximize health benefits for residents. The research not only theoretically supports the importance of community parks in promoting health benefits but also provides practical guidance for urban planners and policymakers in designing and renovating community parks. By considering the multidimensional characteristics of community parks and their non-linear impacts on residents’ health benefits, this research helps to advance the understanding of how community parks can be optimized to enhance the well-being of urban residents. The results suggest that in high-density urban areas, community parks can serve as important green infrastructure for promoting health and sustainability. Therefore, this research contributes to the broader goals of urban sustainability and residents’ well-being by providing evidence-based recommendations for community park micro-renewal.